Aesthetic dimension of political advertising - Liutko, Natalia (Torun International Studies, 2015)
Political advertising is a form of aesthetic and political communication; it is encountered in election, addressed to electoral groups and aimed at electoral behavior perception management. Aesthetic and political communication has a lot of characteristics of political communication in general, that in its turn is a kind of public communication. Advertising nails down certain emotions in the person’s memory, which hereafter will determine his (her) behavior. Achieving of an objective is made by aesthetic images creation and advancement that facilitates aesthetic judgment of objective world, increases beauty sensitivity, uprears and develops cultural perception, the sense of taste. In the course of it, the didactic orientation of political advertising emerges. In a general sense, political advertising aesthetics is the aesthetics of personal behavior management technologies in social setting, the aesthetic of personal influence. Political events infer aesthetic expressiveness and legalization in response to mass media, publicity, popular art, word-picture and image. Internal action of political and aesthetic aspects turns the individual into spectator and recipient.